STITCH PER INCH MEASUREMENT USING IMAGE PROCESSING TECHNIQUES - Andrian Wijayono; Valentinus Galih Vidia Putra (Arena Tekstil, 2018)
Stitch per inch is defined as the one of many quality parameters which evaluated in the garment industry. The strength of the stitch will be determined by stitch per inch, both on the clothes and fabrics. Conventionally, stitch per inch determined by using a traditionaly visual method. Many researchers have been developed the image processing technology which applied into various textile fields. In this reserach, it has been developed a new method and a new software which could determine stitch per inch on fabrics using the image processing techniques. Stitch per inch measurement has been done using the box counting method (pixel) on image processing software. Stitch per inch in several fabrics (with different color and structures) has been measured, which shows that the value of the each methods are equal